High performance communication redundancy in a digital substation based on IEC 62439-3 with a station bus configuration - Kumar, S.; Das, N.; Islam, Syed (2015)
High speed communication is critical in a digital substation from protection, control and automation perspectives. Although International Electro-Technical Commission (IEC) 61850 standard has proven to be a reliable guide for the substation automation and communication systems, yet it has few shortcomings in offering redundancies in the protection architecture, which has been addressed better in IEC 62439-3 standard encompassing Parallel Redundancy Protocol (PRP) and High-Availability Seamless Redundancy (HSR). Due to single port failure, data losses and interoperability issues related to multi-vendor equipment, IEC working committee had to look beyond IEC 61850 standard. The enhanced features in a Doubly Attached Node components based on IEC 62439-3 provides redundancy in protection having two active frames circulating data packets in the ring. These frames send out copies in the ring and should one of the frame is lost, the other copy manages to reach the destination node via an alternate path, ensuring flawless data transfer at a significant faster speed using multi-vendor equipment and fault resilient circuits. The PRP and HSR topologies provides higher performance in a digitally protected substation and promise better future over the IEC 61850 standard due to its faster processing capabilities, increased availability and minimum delay in data packet transfer and wireless communication in the network. This paper exhibits the performance of PRP and HSR topologies focusing on the redundancy achievement within the network and at the end nodes of a station bus ring architecture, based on IEC 62439-3.